English in the Current Scenario: An Analytical Reading of Globalisation Through the Lens of Language - Aby John; Emil George (Progress in Language, Literature and Education Research Vol. 7, 2024)
This research article explores the role of English in the process of globalization. This article also delves into the depth of the possible implications of emergence of other languages as world language/global language under the influence of globalization. In order to understand the influx of globalization on humanity, this study examines the significance of the English language in the context of globalization. Certain aspects like the advantages of having English as a global language, the risk factors it possesses and the different varieties of English/World Englishes are analysed in this article.